A EDUCAÇÃO PROFISSIONAL E A POLÍTICA PÚBLICA MULHERES MIL: a implementação no âmbito do IFMA em São Luís - Silva, Tássia Mendes e (2015)
This work intended to study public policy Thousand Women from the experience of the Federal Institute of Maranhão, São Luís, from 2009 to 2012, which was aimed at raising the educational level and the qualification of participants. It was an inclusive public policy, with a gender approach, geared to the provision of vocational training courses, which sought to provide women in vulnerable social conditions access to education, qualifications, employment and income through vocational training and citizen. This paper considered the historical inequalities faced by women in Brazilian society, particularly with regard to access to education, qualification and entry into the labor market. The research was of bibliographical and documentary evidence, to identify the key aspects in government discourse and verification of what happened in the concrete reality of the students of the courses. A theoretical review was carried out on the main categories present in this policy, such as education, professional training, citizenship, sustainable development, equity, work, public policy and gender. Was achieved as a result note that the actions taken in this policy achieved some objectives pursued without getting the complete success of its initial proposal, as the rise of education and the integration into the majority of the labor market of the students, although it was for some students important for raising the self-esteem, to return to their studies and to enter the job market.